Problems of Using Google Classroom as an Instructional Media in Business Administration Students (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The purposes of this study were 1) to investigate problems of using Google Classroom as aninstructional media in Business Administration students, and 2) to study additionalsuggestions from respondents. The research samples were 75 Business Administrationstudents during the second semester of academic year 2021 derived through Simple RandomSampling technique. The instruments for collecting the data were the rating-scale and openendedquestionnaire. Frequency, percentage, mean, standard deviation and content analysiswere used for data analysis. The findings were as follows: the students had a low level ofproblems of using Google Classroom as an instructional media in overall. When consideringeach aspect, the lowest rank was Teaching materials, followed by Accessibility and Learningactivities; the respondents suggested that using Google Classroom is less effective than aface-to-face meeting; the students are not comfortable with the lack of interaction with otherlearners or a teacher; the students have several inabilities to work with computers orsmartphones; the students have eye strain when learning with Google Classroom; the studentshave a low internet bandwidth; and the students have too many distractions, e.g., games,social media.